THE INFLUENCE OF BRAND IMAGE, SOCIAL INFLUENCE AND PRODUCT PRICE WITH TRUST AS MEDIATING VARIABLES ON THE PURCHASE INTENTION OF 'RAJA DIMSUM' CULINARY MSMES IN GENERATION Z IN PADANG CITY: PENGARUH BRAND IMAGE, SOCIAL INFLUENCE DAN PRODUCT PRICE DENGAN TRUST SEBAGAI VARIABEL MEDIASI TERHADAP PURCHASE INTENTION UMKM KULINER ‘RAJA DIMSUM’ PADA GENERASI Z DI KOTA PADANG - Putri Yasmin Al Adawiyyah; Rosyeni Rasyid (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The large number of culinary industry MSMEs that are developing at this time does not guarantee to avoid problems that affect their growth. Likewise, what was passed by “Raja Dimsum”, Culinary MSMEs which had several obstacles when running their business. This study aims to determine the effect of Brand Image, Social Influence and Product Price on Purchase Intention of UMKM Culinary 'Raja Dimsum' in Generation Z in Padang City. This research sampling technique with certain criteria. The research participants totaled 170 respondents who were selected as samples. Data were collected through online questionnaire distribution and then analyzed using SmartPLS 3.0 software. The results of this study reveal that (1) brand image has no direct effect on purchase intention, (2) social influence has a significant positive effect on purchase intention, (3) product price has a significant positive effect on purchase intention, (4) trust has a significant positive effect on purchase intention, (5) brand image has no direct effect on trust, (6) social influence has a significant positive effect on trust (7) product price has a significant positive effect on trust (8) brand image has no effect on purchase intention mediated by trust (9) social influence has a significant positive effect on purchase intention mediated by trust (10) product price has a significant positive effect on purchase intention mediated by trust.